THE ANALYSIS OF LITERAL TRANSLATION METHOD ENGLISH INTO INDONESIAN IN SHORT STORY ENTITLED “MERCURY AND THE CARPENTER” - Nuraeni Mutaqin; Wati Sulistyawati; Agus Rahmat (IKIP Siliwangi, 2020)
The purpose of this research is to know whether there are literal translation method used in the short story entitled Mercury and the Carpenter or not. This study used qualitativee descriptive research. The source of this research used document of short story entitled “Mercury and the Carpenter” either in English or Indonesian written by Sergius Lesky. As for the limitation, this research is only analyzing about method of literal translation. In collecting data, the researhcer read the short story both in English and Indonesian, then analyzed the method of literal transation. In analyzing data, the researcher used the method of document analyzing with taxonomy analysis, in the other word, the researcher classified the data into the method of literal translation. Based on the data analysis “Mercury and the Carpenter”, the researcher had founded 8 data of Literal translation method.Keywords: Translation, Method, and Short Story.